The Tradition of Walimah Al-‘Urs Across Time: a Study of the Prophet’s Hadith and Reflections on the “Marriage is Scary” Phenomenon - Umami, Nadia ilma; Machmudah Lailiyah; Asqina Haudlatul Ashfa; Mohammad Hamsa Fauriz (MADINAH, 2025)
The phenomenon of “marriage is scary,” which is increasingly prevalent among urban youth, reflects deep structural and psychological concerns about the institution of marriage. These concerns are closely linked to economic pressures, high social expectations, and interpersonal challenges shaped by personal experiences or social environments. This study aims to explore the cultural and religious roots of marriage traditions, with a particular focus on walimah al-‘urs, through historical and thematic analysis of the Prophet Muhammad’s ﷺ hadiths. The study employs a qualitative descriptive approach, utilizing library research methods to systematically collect, examine, and interpret primary sources from canonical hadith collections (Sahih al-Bukhari, Sahih Muslim) and classical commentaries (‘Umdat al-Qari, Sharh Sahih al-Bukhari). Secondarysources include contemporary literature in psychology, sociology, and gender studies, as well as statistical data from official institutions, to contextualize the findings within modern sociopsychological realities. Data analysis follows a thematic-descriptive framework, identifying relevant hadiths that provide normative guidance on marriage celebrations. Three key hadiths were identified from Sahih Bukhari and Sahih Muslim that illustrate the Prophet’s ﷺ principles regarding walimah, emphasizing flexibility, simplicity, and modesty in its practice. The study contributes both theoretically and practically. Theoretically, it provides a nuanced understanding of how prophetic traditions can inform contemporary marriage practices. Practically, it offers a spiritual and social alternative to the modern pressures of marriage culture, particularly the tendencies toward materialism and social performance, thus fostering resilience and a balanced perspective for young Muslims navigating marital expectations